Hubungan Penyuluhan Pertanian Terhadap Peningkatan Produksi Petani Padi (Kampung Marga Mulya, Distrik Semangga) Kabupaten Merauke - Anggraheni, Naning Dwi; Widyantari, Ineke Nursih; Untari, Untari (Musamus University, 2021)
This study aims to determine the relationship between agricultural extension workers and farmers' rice production in Marga Mulya Village, Semangga District, Merauke Regency. This research is a descriptive survey research using Likert scale analysis. then analyzed using Pearson Product Moment (PPM) analysis with a total sample of 83 respondents from a total population of 493 people. The results of this study indicate that agricultural extension provides a significant /noticeable to increased the farmers rice production in Marga Mulya Village, it can be seen from the calculation results analysis shows that the value of t = 8.949 is greater than the value of t table = 1.989, while the contribution of the agriculture instructor relationship to increase rice production by 49.7% as determined by HR and the remaining 50.3% is influenced by other variables not included in the model of Pearson Product Moment correlation analysis such as climatic conditions, capital farm management.